Understanding assertion and truth in relation to metaphor - Kwesi, Richmond (Department of Philosophy, 2017)
The central question I engage with in this dissertation is this: are declarative metaphorical sentences truth-evaluable? I pursue an affirmative answer to this question within a pragmatic framework that does not (1) reduce the metaphorical to the literal, (2) appraise the metaphorical in terms of the literal, and (3) provide a sui generis kind of 'metaphorical truth'. In presenting this answer, I show, on the one hand, that other positive responses in terms of speaker meaning (Searle 1993; Moran 1989; Camp 2006) and pragmatic enrichment (Bezuidenhout, 2001; Recanati 2004) are inadequate, and, on the other hand, that the main reasons proffered for the denial of the truth-aptness of metaphorical sentences, in the literature, are unsatisfactory. I do this by arguing, in Chapter I, that characterizing metaphor in seeing-as experiential or phenomenological terms is not incompatible with appraising metaphors for truth when the notion of understanding metaphors is construed in terms of ability to use them; in Chapter II, that a causal explanation of metaphors (Davidson, 1979; Cooper, 1984; Rorty, 1987; Lepore & Stone, 2010) does not successfully justify denial of the content of metaphors, and that the normative practices involved in the use of metaphors – engaging in genuine disagreements, using metaphors in reasoning, endorsing and retracting metaphors – attest to the fact that associated with metaphors are contents that are propositional in nature. In Chapters III and IV I argue that the pragmatic criterion – inviting others to do something (Lamarque & Olsen, 1994; Blackburn, 1984, 1998), the psychological criterion – non-expression of belief (Blackburn, 1984; Davies 1984), and the semantic criterion – non-assertion of claims (Loewenberg, 1975; Davies 1982), are all not appropriate determinants of the truth-evaluability of metaphors. To evaluate metaphors qua metaphors for truth, I draw on Brandom's (1983, 1994, 2000) inferentialist pragmatics, in Chapter V, in providing an articulation of the use of metaphors in terms of inferring and the undertaking of commitments. The overall thesis for this dissertation is that, an inferential articulation of metaphors that approaches the central question from the pragmatics of what we do in using metaphors is apt for understanding metaphorical sentences as propositionally contentful and truth-evaluable.